CLASSICAL PRESENTATION OF DARIER’S DISEASE: A RARE DISORDER OF KERATINISATION - Mahboob, Atiya; Yaqub, Faryal; Shahzad, Zahid; Afzaal, Manaal; Hanif, Moazzum; Khan, Deeba Sattar; Nasim, Riffat; Khan, Aleena (Journal of Ayub Medical College Abbottabad, 2010)
Keratosis follicularis or Darier’s disease (DD), a rare autosomal dominant disorder is characterised clinically by appearance of multiple, prurutic, discrete, scaly papules affecting seborrheic areas coupled with palmar pits, nail changes and mucosal involvement. Histologicaly the lesions show suprabasal clefts with acantholytic and dyskeratotic cells. We report a case of 35 years old woman with typical clinical and histological features of Darier’s disease. Keywords: Autosomal dominant, palmar pits, suprabasal clefts, Darier’s disease